What is students’ perception of Flipped Classroom usage during Emergency Remote Teaching of Software Engineering subjects? An Experience Report in Brazil - Alves, Gabriela; Soares, Pamella; Souza, Bianca; Veras, Nécio; Araújo, Allysson Allex (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
Emergency Remote Teaching (ERT) resulting from the COVID-19 pandemic reinforced multiple pedagogical challenges in the context of Software Engineering (SE) in Brazil. Then, an incessant reflection on how to engage students in a classroom that strengthens learning becomes vital, for example, through active teaching methods, such as the Flipped Classroom (FC). Given this motivation, this work aims, under the scope of an experience report, to investigate the perception of students on the use of FC during ERT of Software Engineering, Requirements Engineering, and Software Project Management taught at the Federal University of Ceará (UFC - Campus Crateús). Characterized as descriptive and quali-quantitative, this research approached questionnaires and focus groups as data collection methods. We found that, when asked about the contribution of FC to learning process during ERT, 97.2% of the students expressed their total or partial agreement. Qualitative results also evidence pertinent observations about the benefits and challenges of using FC in the ERT. As the main contribution, we provide an empirical reflection on the adoption of FC, whose learnings may be relevant to increasing the debate around the pedagogical developments in the post-pandemic period of SE education.